Relationships between community public service facilities and social capital: An exploratory study of Harbin, China - Yichen Luo; Guangtian Zou; Qianyu Liu (PLoS ONE, 2025)
Social capital is closely intertwined with neighborhood environments and facility provisions. It is a vital resource for supporting residents’ happiness and satisfaction. In the context of urban stock development and the concentrated construction of community public service facilities, it remains unclear whether the spontaneous construction of facilities follows a colocation model and how facility-related construction affects residents’ quality of life. In this study, we used a questionnaire survey to analyze social capital, summarizing it into aspects such as community cohesion, social support, community trust, and sense of belonging. Then, we acquired the points of interest for facilities in Harbin, China, computed the Global Colocation Quotient (GCLQ) and Local Colocation Quotient (LCLQ), the proportion of spatial units occupied by facilities, and the Shannon diversity index, and analyzed the patterns. Aged care services, childcare centers, and community cultural services were found to have the strongest mutual attractions. Finally, an ordinary least squares model was constructed. The proportion of spatial units occupied by community public service facilities was closely related to social capital growth. In the relationship between the colocation model and social capital, LCLQ-healthcare showed a negative correlation, LCLQ-aged care and LCLQ-childcare showed a positive correlation, and LCLQ-cultural and sports showed a positive correlation with a sense of community belonging. The geographically weighted regression model indicated significant spatial heterogeneity in how facility-related construction affects social capital. This study offers a foundation and reference for the sustainable planning and development of integrated community public service facilities.